Not so biodegradable: Polylactic acid and cellulose/plastic blend textiles lack fast biodegradation in marine waters. - Sarah-Jeanne Royer; Francesco Greco; Michaela Kogler; Dimitri D Deheyn (PLoS ONE, 2023)
The resistance of plastic textiles to environmental degradation is of major concern as large portions of these materials reach the ocean. There, they persist for undefined amounts of time, possibly causing harm and toxicity to marine ecosystems. As a solution to this problem, many compostable and so-called biodegradable materials have been developed. However, to undergo rapid biodegradation, most compostable plastics require specific conditions that are achieved only in industrial settings. Thus, industrially compostable plastics might persist as pollutants under natural conditions. In this work, we tested the biodegradability in marine waters of textiles made of polylactic acid, a diffused industrially compostable plastic. The test was extended also to cellulose-based and conventional non-biodegradable oil-based plastic textiles. The analyses were complemented by bio-reactor tests for an innovative combined approach. Results show that polylactic acid, a so-called biodegradable plastic, does not degrade in the marine environment for over 428 days. This was also observed for the oil-based polypropylene and polyethylene terephthalate, including their portions in cellulose/oil-based plastic blend textiles. In contrast, natural and regenerated cellulose fibers undergo complete biodegradation within approximately 35 days. Our results indicate that polylactic acid resists marine degradation for at least a year, and suggest that oil-based plastic/cellulose blends are a poor solution to mitigate plastic pollution. The results on polylactic acid further stress that compostability does not imply environmental degradation and that appropriate disposal management is crucial also for compostable plastics. Referring to compostable plastics as biodegradable plastics is misleading as it may convey the perception of a material that degrades in the environment. Conclusively, advances in disposable textiles should consider the environmental impact during their full life cycle, and the existence of environmentally degradable disposal should not represent an alibi for perpetuating destructive throw-away behaviors.